Prevalence and Association of Malaria With ABO Blood Groups in Bosaso City, Puntland, Somalia: A Cross‐Sectional Study - Yahye Isse Hassan; Mohamed Said Hassan (Health Science Reports)
ABSTRACT Background and Aims Malaria remains a global health concern, with an estimated 249 million cases annually and 2.2 billion people at risk of infection. This study aimed to investigate the association between malaria species and ABO blood groups and identify the relationship between ABO blood groups and parasitemia. Methods A cross‐sectional study was conducted in Bosaso, Puntland, Somalia, from November 2022 to May 2023. Data were collected through simple random sampling involving 201 confirmed malaria cases from the national hospital. Blood samples obtained via finger prick were prepared as thick and thin smears, stained, and examined microscopically. Statistical analysis included descriptive statistics, Chi‐square, and ANOVA tests to assess associations between malaria species, blood groups, and parasitemia. Results The prevalence of Plasmodium species was as follows: P. falciparum (48%), P. vivax (41%), and others (10%). Older age groups (31–45 and 46–60 years) exhibited higher prevalence rates for P. falciparum (50.7%–80.8%), while younger participants demonstrated increased susceptibility to P. vivax. Blood groups B (24%) and AB (18.8%) presented lower P. falciparum prevalence, whereas blood groups A (55.4%) and O (54.7%) displayed higher prevalence rates. Significant associations were observed between age groups and Plasmodium species (χ² = 14.2, p = 0.027; F = 4.848, p = 0.030) and between blood groups and Plasmodium species (χ² = 23.9, p = 0.001; F = 3.583, p = 0.015). A relationship between blood groups and parasitemia was also identified (χ² = 17.4, p = 0.008; F = 12.79, p = 0.017). Conclusion The findings of this study not only underscore the higher risk of P. falciparum in older individuals but also provide crucial insights into the interplay between malaria and ABO blood groups. This knowledge is significant for enhancing community awareness and implementing effective management strategies to reduce the risk of malaria, thereby enlightening the reader about the potential impact of this research.